Magnetic induction catalytic reverse water-gas shift method
By loading a mechanical composite grinding tablet with magnetic induction catalyst and white carbon black in the reverse water gas transformation reaction, the catalyst is self-heating and self-catalyzing with alternating magnetic fields, solving the problems of high-temperature sintering and high energy consumption in traditional technologies, and achieving low energy consumption, high economical and green catalytic reactions.
Patent Information
- Application Number
- CN202311040395.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-17
- Publication Date
- 2025-02-25
AI Technical Summary
The prior art has problems such as catalyst sintering inactivation and high energy consumption in the counterwater gas transformation reaction, making it difficult to achieve a green catalytic reaction with low energy consumption and high economic efficiency.
The magnetic induction catalyst is used to autocatalyze the alternating magnetic field, combining the thermal conductivity and chemical stability of white carbon black to achieve the "charge-spin" synergistic effect of the catalyst to carry out the reverse water gas transformation reaction.
The catalyst self-heating and self-catalyzing is achieved at low ambient temperature, reducing reaction energy consumption, improving energy utilization and economic benefits, and avoiding the sintering inactivation problem caused by traditional high-temperature heating.
Smart Images

Figure CN119499979A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of energy chemical catalysts and relates to a catalyst and a method for magnetic induction catalytic reverse water-gas shift. Background Art
[0003] With the increasing scarcity of petroleum resources and the increasingly tense international energy market, the use of CO2 as a carbon source to synthesize fuels and high-value-added chemicals is one of the important ways to utilize CO2 chemical conversion. Among them, the reverse water-coal shift reaction (RWGS) is considered to be one of the most promising methods for utilizing carbon dioxide due to its high selectivity and low operating pressure, because it has great potential in the subsequent synthesis of methanol and olefins after converting carbon dioxide into synthesis gas. This conversion reaction is a typical endothermic process, and increasing the reaction temperature is conducive to the reaction. However, the traditional resistance external heating to increase the system temperature not only aggravates the sintering of the active metal center, but also aggravates the energy consumption. In recent years, with the rapid development of renewable energy power generation technology, there is great potential for developing electricity as the main energy supply in long-term catalytic processes. In industrial catalytic reactions, energy efficiency, suitability of reaction conditions and adaptability to intermittent energy supply have become increasingly important parameters. In this case, magnetic induction provides the possibility of directly heating magnetic metal materials, using magnetic metal materials as both catalytic active centers and magnetic induction heating centers, and completing the subsequent catalytic reaction in a very local, rapid and energy-saving manner, saving the energy consumption of heating the entire reactor environment, resulting in a milder overall process temperature and lower energy consumption. The non-direct contact heating of the induction catalytic reaction can control the induction heating depth and the selected material heating area, realize the body heating method of the material, and improve the uniformity of the temperature field distribution in the thickness direction of the material. Therefore, the induction catalytic direct hydrogenation synthesis gas process using CO2 as raw material at low ambient temperature has opened up a new process route with good development prospects for the rapid production of synthesis gas from CO2 with low energy consumption, high economy, greenness and optimization of my country's energy structure. It can not only alleviate climate change on a global scale, but also provide ideas for the energy crisis.
[0004] The large amount of CO2 emissions has already had a serious negative impact on the climate, so how to reduce the pressure of CO2 emissions has attracted the attention of many researchers. British Petroleum (BP) pointed out that it is expected that CO2 emissions will need to be reduced by 800Gt by 2050. Reducing CO2 emissions is a long-term and extensive task. Generally, there are three possible strategies: reducing CO2 production, CO2 storage, and CO2 utilization. The first strategy requires improving energy efficiency and switching from fossil fuels to low-carbon intensive energy such as hydrogen and renewable energy. Due to many problems, this strategy is difficult to implement. CO2 storage includes the development of new technologies to capture and isolate carbon dioxide. This process is relatively mature, but the strategy requires a relatively high cost and has the potential to cause harm to the ecology and environment. As a safe, economical, and renewable carbon source, CO2 is very attractive to be converted into high-value-added products using chemical methods. It can not only alleviate climate change caused by the increase in CO2 concentration in the atmosphere, but also reduce the pressure of fossil fuel consumption and realize the effective circulation of carbon resources. Therefore, more and more attention is focused on the conversion of CO2.
[0005] CO2 is a highly symmetrical linear molecule with stable chemical properties. It is relatively difficult to activate CO2 and convert it into other carbon-containing compounds. High temperature must be applied externally to activate CO2 molecules under high temperature (or high temperature and high pressure) conditions to convert them into other chemicals. The new low ambient temperature IC-RWGS process is a non-contact heating catalytic technology that can control the material heating depth and the selected material heating area, and is easy to achieve high power density. It has the advantages of low energy consumption, high heating efficiency, high heating temperature and fast response speed. The development of the new IC-RWGS process avoids problems such as external high temperature and uneven heating. At the same time, cheap, environmentally friendly, and naturally abundant transition metals are used as catalysts. It is expected to maintain high CO2 conversion rate and synthesis gas selectivity while reducing the energy consumption of the reaction process and improving economic benefits.
[0006] The RWGS reaction is an endothermic process, and high temperature is conducive to the forward reaction. It often requires high temperature (>500°C) operation to suppress the occurrence of side reaction methanation and ensure high CO2 conversion rate and high CO selectivity.
[0007] At present, the research on catalysts used in RWGS reactions mainly includes two categories: precious metal catalysts (Ir, Au, Pt, etc.) and non-precious metal catalysts (Cu, Ni, Fe, etc.). These two types of metals also have many problems in catalyzing RWGS reactions, namely, high temperature environments easily induce catalyst sintering and deactivation, large amounts of energy consumption, and high requirements for equipment and materials. Due to the low amount of precious metal resources, high production costs, and the tendency to have deactivation behaviors such as carbon deposition during the RWGS reaction, it is difficult to produce CO economically and sustainably; compared with precious metals, although non-precious metals are cheap, they have high temperature requirements (≥600°C) in the reaction and poor thermal stability, and are very easy to sinter and deactivate, resulting in low catalytic efficiency.
[0008] In summary, it is still a major challenge to achieve a low-energy, high-economic, safe and green low-temperature reverse water-gas shift reaction in an exothermic system. Summary of the invention
[0009] In order to overcome the problems in the prior art, the purpose of the present invention is to provide a method for magnetic induction catalytic reverse water-gas shift, which has low energy consumption and is safe and green.
[0010] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0011] A method for magnetic induction catalytic reverse water-gas shift, comprising the following steps:
[0012] The magnetic catalyst and white carbon black are pressed into tablets to obtain a catalyst;
[0013] The catalyst is placed in the induction coil area of the induction heating equipment, and a mixture of CO2 and H2 is introduced to perform a reverse water-gas shift reaction. The reaction pressure is normal pressure, and the alternating frequency is 50-300KHz to produce CO.
[0014] Furthermore, the flow rate ratio CO2:H2=3:1.
[0015] Furthermore, the diameter of the catalyst is 0.425-0.850 mm.
[0016] Furthermore, the magnetic catalyst is prepared by the following process: a non-precious metal salt, a metal element, an organic ligand and a solvent are mixed evenly, and then the pH is adjusted to 5, and the mixture is allowed to stand for 20-30 hours or crystallized at 120-180°C for 15-72 hours, centrifuged, washed, and dried to obtain a metal precursor material; the metal precursor material is heat-treated and carbonized at 400-600°C for 2-10 hours under an inert atmosphere to obtain a magnetic catalyst.
[0017] Furthermore, the non-noble metal salt is ferric chloride, ferrous chloride, ferric nitrate, cobalt chloride, cobalt nitrate or nickel nitrate.
[0018] Furthermore, the metal element is Fe; the solvent is one of water, ethanol and N,N-dimethylformamide; and the organic ligand is terephthalic acid or trimesic acid.
[0019] Furthermore, the molar ratio of the non-noble metal salt to the organic ligand is 1:1; the molar ratio of the metal element to the organic ligand is 1:1; and the inert atmosphere is argon.
[0020] Furthermore, the magnetic catalyst is prepared by the following process: polyvinyl pyrrolidone, water and ethanol are stirred evenly, and then a metal salt is added to obtain a mixed solution, potassium ferrocyanide solution is added to the mixed solution, and after mixing evenly, the mixture is allowed to stand for 24 hours, centrifuged, and dried to obtain a metal precursor material, and the metal precursor material is heat-treated at 300-700°C for 2-6 hours under an inert atmosphere to obtain a magnetic catalyst.
[0021] Furthermore, the usage ratio of polyvinyl pyrrolidone, water, ethanol, metal salt and potassium ferrocyanide is 5g:30mL:90mL:10mmoL:5mmol.
[0022] Furthermore, the metal salt is cobalt acetate, nickel acetate or ferrous chloride; and the metal precursor material is heat treated at 300-700° C. for 2-6 hours under an inert atmosphere, and the inert atmosphere is nitrogen.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] In the present invention, the derived magnetic catalytic material and white carbon black (WCB) are mechanically composite-ground and pressed into a quartz tube, which is placed in an alternating magnetic field environment to achieve the "charge-spin" synergy of the catalyst, and self-heating and self-catalysis promote the reverse water-gas shift reaction, thereby achieving the purpose of producing synthesis gas with low energy consumption and high economy. Based on the advantages of WCB such as good thermal conductivity, chemical stability, electrical insulation, high temperature resistance, high specific surface area and multiple pores, WCB is selected as a diluent filler and compacted with the catalyst to maintain the volume stability of the catalyst in the induction heating equipment. In the present invention, induction heating catalysis does not require external high temperature, showing the advantages of low system temperature and low energy consumption. The induction heating catalytic reaction has high energy utilization, uniform temperature distribution and high system heat transfer efficiency, and the induction catalytic system equipment is simple and the process is safe and controllable.
[0025] Furthermore, since induction catalysis is a non-direct contact technology that uses electromagnetic energy to act on charges and electron spins of ferromagnetic materials in an alternating magnetic field, and the magnetic properties of Fe and Co materials are good, the metal materials prepared from Fe and Co salts can promote the fine coordination of charge transfer and spin selection in a magnetic field, and ultimately achieve the purpose of self-heating and self-catalysis of materials without external high temperature. Using non-precious metal salts and metal elements as raw materials, the prepared catalyst can significantly improve the economic benefits of producing synthesis gas because of the use of cheap and readily available non-precious metal salts as catalyst raw materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 Schematic diagrams of heat transfer by conventional external heating and heat transfer by induction internal heating of the present invention, wherein (a) is a schematic diagram of heat transfer by conventional external heating, and (b) is a schematic diagram of heat transfer by induction internal heating;
[0027] Figure 2 VSM diagram of magnetic material FeCo / C at 300K;
[0028] Figure 3 is the XRD pattern of the magnetic material FeCo / C;
[0029] Figure 4 The RWGS catalytic performance comparison chart of precious metals, non-precious metals and FeCo composite materials;
[0030] Figure 5 Schematic diagram of the reaction apparatus. DETAILED DESCRIPTION
[0031] In order to facilitate the understanding of the present invention, the present invention will be described more fully below with reference to the relevant drawings. The preferred embodiments of the present invention are given in the drawings. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present invention more thoroughly and comprehensively understood.
[0032] A method for magnetic induction catalytic reverse water-gas shift of the present invention comprises the following steps:
[0033] The magnetic catalyst is filled into a quartz tube, and the quartz tube is placed in the induction coil area of the induction heating equipment. The reaction pressure is normal pressure, the reaction temperature is the system temperature generated by the magnetic catalyst itself, the alternating frequency is 50-300KHz, and the raw material gas flow rate ratio is CO2:H2=3:1. The mixed gas enters the quartz tube containing the magnetic catalyst to perform a reverse water gas shift reaction to produce CO.
[0034] The system temperature generated by the magnetic catalyst itself in the present invention is related to the catalyst itself. The more the catalyst is used, the higher the temperature is. By adjusting the type and amount of the catalyst, the temperature can be any degree. When the magnetic material is in an alternating magnetic field, the magnetic moment will change with the direction of the magnetic field, and the energy generated by the change of the magnetic moment of the magnetic material will be released in the form of heat (that is, the hysteresis thermal effect).
[0035] The alternating magnetic field directly acts on the magnetic catalyst without the need to externally heat the entire system, resulting in the system having the characteristics of low ambient temperature, low energy consumption and high energy utilization.
[0036] The preparation method of magnetic catalyst is as follows:
[0037] At room temperature, a non-precious metal (Fe, Co or Ni) salt, a metal element, an organic ligand and water / ethanol / N,N-dimethylformamide (DMF) are stirred for 1 hour to be fully mixed, and KOH is used to adjust the pH to 5. After the solution is evenly mixed, it is transferred to an autoclave with a polytetrafluoroethylene liner and crystallized at 120-180°C for 15-72 hours, or it is allowed to stand at room temperature for 20-30 hours. After crystallization or standing, centrifugal separation is performed, and it is washed with deionized water and ethanol for 3-4 times respectively, and then placed in an oven to dry. After drying, a metal precursor material is obtained. The obtained precursor material is placed in a quartz tube, and heat-treated and carbonized at 400-600°C for 2-10 hours under an inert atmosphere (Ar gas) to obtain a magnetic catalyst.
[0038] Wherein, the non-noble metal (Fe, Co or Ni) salt is ferric chloride, ferrous chloride, ferric nitrate, cobalt chloride, cobalt nitrate or nickel nitrate.
[0039] The metal element is Fe;
[0040] The organic ligand is terephthalic acid (BDC) or trimesic acid (BTC);
[0041] The molar ratio of the non-noble metal salt to the organic ligand is 1:1;
[0042] The molar ratio of metal element to organic ligand is 1:1.
[0043] Or the preparation method of magnetic catalyst is as follows:
[0044] 5g of polyvinyl pyrrolidone (complexing agent) (PVP, molecular weight of 4000) was stirred evenly with 30mL H2O and 90mL ethanol, and then 10mmoL of cobalt acetate (Co(AC)2·6H2O), nickel acetate or ferrous chloride was added thereto, and stirred for 5min to obtain a uniform mixed solution. Then, 5mmol of potassium ferrocyanide (K3[Fe(CN)6]) was completely dissolved in 60mL H2O, and then added dropwise to the uniform mixed solution. After stirring for 1h, the mixed solution was allowed to stand at room temperature for 24h. After centrifugation, the catalyst was washed with deionized water and ethanol for 3-4 times respectively, and the washed catalyst was placed in an oven to dry. After drying, a metal precursor material was obtained, which was recorded as FeCo-MOF, FeNi-MOF or FeFe-MOF. The metal precursor material MOF obtained above was placed in a quartz tube, and the tube was purged with an inert atmosphere (N2) for 2h. Then, heat treatment is performed at 300-700° C. in the atmosphere for 2-6 hours to obtain a magnetic catalyst, namely, FeCo / CN, FeNi / CN or FeFe / CN.
[0045] The magnetic catalyst and white carbon black (WCB) are pressed into tablets to obtain a catalyst with a diameter of 0.425 to 0.850 mm.
[0046] A reverse water-gas shift catalyst with magnetic properties is prepared by a series of synthesis methods using magnetic non-precious metal salts or simple substances as preparation raw materials, so that in the magnetic induction catalytic system, the magnetic catalyst is both an active component and a heating component.
[0047] The catalyst in the present invention can be prepared by using common catalyst preparation methods such as hydrothermal synthesis, sol-gel method, coprecipitation method and mechanical mixing method.
[0048] The catalyst of the present invention has high reversible saturation magnetization, high magnetic permeability, large residual saturation induction and hysteresis.
[0049] Example 1
[0050] CoCl2·6H2O, Fe powder, trimesic acid and deionized water were added to a beaker in a molar ratio of 1:1:1:80 and stirred until a uniform viscous paste mixture was obtained. Then 1.44 ml of KOH solution (10 mol / L) was added to the obtained mixture, the pH value was adjusted to about 5, and stirred for 2 h to partially remove the protonated tricarboxylic acid. Then it was transferred to a hydrothermal autoclave and crystallized at 180 ° C for 72 h. After cooling, the powder was obtained by high-speed centrifugation and washed several times with deionized water and C2H5OH respectively. Then, the obtained product was dried at 80 ° C for 12 h to obtain the precursor FeCo-MOF material, which was recorded as MIL-45b. The above-mentioned precursor MOF material MIL-45b was placed in a quartz tube and the pipeline was purged with an inert atmosphere (Ar gas) for 2 h. Then, it was heat treated at 600 ° C in this atmosphere for 10 h to obtain the derived magnetic catalytic material FeCo / C.
[0051] Example 2
[0052] 5g of polyvinyl pyrrolidone (PVP, molecular weight 4000) was stirred evenly with 30mL H2O and 90mL ethanol, and then 10mmoL of cobalt acetate (Co(AC)2·6H2O) was added thereto, and stirred for 5min to obtain a uniform mixed solution. Then, 5mmol of potassium ferrocyanide (K3[Fe(CN)6]) was completely dissolved in 60mL H2O and added dropwise to the uniform mixed solution. After stirring for 1h, the uniformly mixed solution was allowed to stand at room temperature for 24h. After centrifugation, the catalyst was washed with deionized water and ethanol for 3-4 times respectively, and the washed catalyst was placed in an oven to dry. After drying, a metal precursor material was obtained, which was recorded as FeCo-MOF. The metal precursor material FeCo-MOF obtained above was placed in a quartz tube, and the tube was purified with an inert atmosphere (N2) for 2h. Then, it was heat treated at 400℃ for 2h to obtain a magnetic catalyst, namely FeCo / CN.
[0053] Schematic diagram of heat transfer in traditional high-temperature thermal catalytic reactions and heat transfer in magnetic induction catalytic reactions Figure 1 As shown in (a) and (b) in the figure, the heat of the traditional catalytic reaction is transferred from the outside to the inside of the catalyst by applying high temperature; the heat of the magnetic induction catalytic reaction is generated by the catalyst itself and transferred from the inside to the outside. Since there is no need to heat the entire reactor, this catalytic method can significantly reduce the heat loss of the reaction.
[0054] The catalyst hysteresis loop (VSM) was obtained by testing on a Lake Shore 7404 vibrating sample magnetometer (USA). Figure 2 As shown, the VSM curve shows the hysteresis phenomenon of the derived carbide composite material, which has obvious ferromagnetic ring behavior at room temperature 300K, indicating that the derived carbide is a ferromagnetic material.
[0055] The powder X-ray diffraction (XRD) results of the catalyst were obtained by testing on a Rigaku Smart Lab diffractometer (Japan). Figure 3 As shown in the figure, the main diffraction peaks of the prepared magnetic catalytic material FeCo / C are located at 44.7° and 65.1°, and these two peak positions correspond to the Fe3Co7 alloy phase, indicating that the catalytic sample has an alloy structure. No characteristic peaks of the phases from Fe2O3 to Co3O4 are clearly observed, which may mean the presence of amorphous Fe and Co oxide phases.
[0056] Catalytic reaction device used in the present invention Figure 5 As shown. The catalytic reaction device includes a cylinder 1, the inner diameter d1 of the cylinder 1 is 8 mm, the outer diameter d2 is 10 mm, the middle outer wall of the cylinder 1 is provided with a heat preservation layer 2, the outer wall of the heat preservation layer 2 is provided with an induction coil 3, the total height h of the induction coil 3 is 25 mm, the diameter d of the induction coil 3 is 20 mm, and a 20-40 mesh magnetic catalyst 4 is provided in the middle of the cylinder 1, and the magnetic catalyst 4 corresponds to the external induction coil 3, and the induction coil 3 has 4 turns in total. An infrared thermometer 5 is provided in the magnetic catalyst 4.
[0057] When the reaction is carried out, the tablet-shaped catalyst is filled in a quartz tube with an inner diameter of 8 mm and an outer diameter of 10 mm. The catalyst filling part is insulated with an insulation layer, and then the insulation area in the quartz is placed at the center of the induction coil with an inner diameter of 20 mm and a coil height of 25 mm. After the magnetic induction device is started, the reaction gas completes the catalytic reaction on the magnetic catalyst in the quartz tube. The temperature of the catalytic system is measured by an external infrared thermometer 5.
[0058] Example 3
[0059] The catalysts obtained in Example 1 and Example 2 were respectively mixed with WCB at a mass ratio of 1:1 by tableting to obtain particles of 0.425-0.850 mm, and 0.6 g of the formed catalyst was filled into the central area of the induction catalytic coil, such as Figure 5 As shown, the induction catalytic reactor is a coaxial reactor made of quartz material, the reaction pressure is normal pressure, the induction amplitude is 12mT, the induction frequency is 78KHz, the flow rate is 40mL / min, and the mixed gas with a flow ratio of CO2 / H2=1 / 3 enters the reaction system.
[0060] The conversion rate of CO2 and the selectivity of each product are calculated by the conservation of carbon atoms. The calculation formula is:
[0061]
[0062]
[0063] In formula (6.1) and formula (6.2), and A i Represent the peak areas corresponding to CO2 and different reaction products, and F i Represent the molar correction factors for CO2 and different reaction products, n i Represents the number of carbon atoms in different reaction products.
[0064] The performance of the catalyst in the present invention is compared with that of the catalyst in the literature, see Figure 4 , Figure 4 In the figure, the green bar graph represents CO selectivity, the dark red dotted line graph represents CO2 conversion, and the blue scatter plot represents the system temperature under this catalytic performance.
[0065] Among them, FeCo / C and FeCo / CN are catalysts for magnetic induction catalytic RWGS reaction. The reaction conditions for the performance of FeCo / C shown in the figure are 245°C, H2:CO2=3, GHSV=8000mL g cat -1 h -1 The reaction conditions for the performance of FeCo / CN shown in the figure are 165℃, H2:CO2=3, GHSV=12000mL g cat -1 h -1 .Ir 0.01 / TiO2、Au 0.01 / TiO2, Pt / La2O2CO3 are commonly used precious metal catalysts in thermal catalytic RWGS reaction. 0.15 / CeO2、Cu 0.1 Fe 0.05 / CeO2 and Ni-CeO2 are commonly used non-precious metal catalysts in thermal catalytic RWGS reactions.
[0066] Ir 0.01 / TiO2 is comparative example 1, Au 0.01 / TiO2 is comparative example 2, 3Pt / La2O2CO3 is comparative example, Cu 0.15 / CeO2 is comparative example 4, Cu 0.1 Fe 0.05 / CeO2 is comparative example 5, Ni-CeO2 is comparative example 6; Comparative example 1Ir 0.01 / TiO2 and comparative example 2Au 0.01 / TiO2 The reaction conditions for the performance shown in the figure are 450°C, 45vol%CO2-45vol%H2-10vol%He mixed gas (total flow rate is 50mL / min); Comparative Example 3 The reaction conditions for the performance shown in the figure of Pt / La2O2CO3 are 380°C, H2:CO2=1; Comparative Example 4 Cu0.15 The reaction conditions for the performance shown in the figure are 600℃, H2:CO2=3, GHSV=400000mL g cat -1 h -1 Comparative Example 5Cu 0.1 Fe 0.05 / CeO2 The reaction conditions for the performance shown in the figure are 600°C, H2:CO2=1; the reaction conditions for the performance shown in the figure of Comparative Example 6Ni-CeO2 are 700°C, H2:CO2=3.
[0067] The two catalysts of Comparative Example 1 and Comparative Example 2 were prepared by wet impregnation method. Using chloroiridic acid (H2IrCl6·6H2O) and chloroauric acid (HAuCl4·4H2O) as raw materials, 0.027g of chloroiridic acid and 0.021g of chloroauric acid were dissolved in 50mL of deionized water, and then 1g of TiO2 was added to the two solutions, and the mixture was stirred at 50°C until the water evaporated. The obtained sample was repeatedly washed with dilute ammonia water (pH=14) and deionized water to remove residual chloride, dried at 60°C for 12 hours, and pretreated in the raw material gas flow at the specified temperature.
[0068] The carrier La2O2CO3 (LOC) of Comparative Example 3 was synthesized using a hydrothermal method. 2g La(NO3)3·6H2O was dissolved in 50mL deionized water, and then 6mL NaOH solution (10wt%) was dropped into the aforementioned solution to obtain a white mixed solution. Subsequently, the white slurry was transferred to a polytetrafluoroethylene autoclave and then hydrothermally heated at 160°C for 12 hours. The solid obtained was filtered, washed with deionized water until neutral, and then dried at 60°C overnight to obtain La(OH)3. After calcination at 500°C in air for 2 hours, LOC was obtained. Pt / LOC was prepared by a traditional impregnation method, and 200mg LOC was ultrasonically dispersed in 20mL deionized water for 5 minutes. Then an appropriate amount of H2PtCl6·6H2O solution (47μL, 0.043mol / L) was added, and then ultrasonically treated for 10 minutes. The sample was then placed in an oil bath and kept at 80°C until all the water evaporated. The prepared sample was then reduced in a tube furnace at 400 °C for 2 h under 5% H2 / Ar to obtain Pt / LOC.
[0069] The two catalysts of Comparative Examples 4 and 5 were prepared by co-precipitation. The pH value of the cerium nitrate solution was adjusted to 2 using oxalic acid, and then ammonia water was added to precipitate cerium oxalate. After heat curing, it was separated, washed, dried at 110°C, and then sintered at 900-1000°C to form cerium oxide. An alcohol solution of Fe(NO3)3·9H2O or / and Cu(NO3)2·2H2O was mixed with cerium oxide, and then the concentrations of iron and copper in the mixture were adjusted to obtain the desired iron / (iron+copper) atomic ratio. The alcohol was evaporated to dryness, and the sample was calcined at 400°C in a muffle furnace for 4 hours to obtain a mono / bimetallic catalyst.
[0070] Comparative Example 6 The catalyst was prepared by coprecipitation. When preparing the Ni-CeO2 catalyst, the mass ratio of Ni / (Ni+CeO2) was 1%. An appropriate amount of nickel nitrate and cerium nitrate were dissolved in deionized water to prepare a 0.50 mol / L mixed solution. NaOH and Na2CO3 were dissolved in deionized water at a molar ratio of 1:1 to prepare a 4 mol / L mixed solution. The two solutions were added dropwise to deionized water and stirred until the pH value was between 9 and 10, and the metal salts were hydrolyzed into hydroxides and carbonates. The precipitate was aged overnight at room temperature. Then, the precipitate was filtered and washed with water several times until the pH value was less than 7.5. The sample was then dried at 80°C for 12 hours and calcined at 800°C for 4 hours to obtain Ni-CeO2.
[0071] Example 4
[0072] Ferrous chloride, Fe powder, terephthalic acid and deionized water were added to a beaker in a molar ratio of 1:1:1:80 and stirred until a uniform viscous paste mixture was obtained. Then 1.44 ml of KOH solution (10 mol / L) was added to the resulting mixture, the pH value was adjusted to 5, and stirred for 2 h to partially remove the protonated acid. It was then transferred to a hydrothermal autoclave and crystallized at 150 ° C for 72 h. After cooling, the powder was obtained by high-speed centrifugation and washed several times with deionized water and C2H5OH respectively. Then, the obtained product was dried at 80 ° C for 12 h to obtain the precursor FeFe-MOF material.
[0073] The precursor FeFe-MOF material was placed in a quartz tube, and the tube was purged with an inert atmosphere (Ar gas) for 2 hours. Then, the tube was heat treated at 600° C. for 10 hours to obtain the derived magnetic catalytic material FeFe / C.
[0074] The derived magnetic catalytic material and white carbon black (WCB) are pressed into tablets to obtain a magnetic catalyst with a diameter of 0.425 to 0.850 mm.
[0075] The magnetic catalyst is filled into a quartz tube, and the quartz tube is placed in the induction coil area of the induction heating equipment. The reaction pressure is normal pressure, the reaction temperature is the system temperature generated by the magnetic catalyst itself, the alternating frequency is 50KHz, and the raw material gas flow rate ratio is CO2:H2=3:1. The mixed gas enters the quartz tube containing the magnetic catalyst to carry out a reverse water gas shift reaction to produce CO.
[0076] Example 5
[0077] Ferric chloride, terephthalic acid and DMF were added to a beaker at a molar ratio of 1:1:80 and stirred until a uniform mixture was formed. Then, it was transferred to a hydrothermal autoclave and crystallized at 150°C for 15 hours. After cooling, the powder was obtained by high-speed centrifugation and washed several times with deionized water and C2H5OH respectively. Then, the obtained product was dried at 80°C for 12 hours to obtain the precursor Fe-MOF material.
[0078] The precursor Fe-MOF material was placed in a quartz tube, and the tube was purged with an inert atmosphere (Ar gas) for 2 hours. Then, the tube was heat treated at 600° C. for 2 hours to obtain the derived magnetic catalytic material Fe / C.
[0079] The derived magnetic catalytic material and white carbon black (WCB) are pressed into tablets to obtain a magnetic catalyst with a diameter of 0.425 to 0.850 mm.
[0080] The magnetic catalyst is filled into a quartz tube, and the quartz tube is placed in the induction coil area of the induction heating equipment. The reaction pressure is normal pressure, the reaction temperature is the system temperature generated by the magnetic catalyst itself, the alternating frequency is 300KHz, and the raw material gas flow rate ratio is CO2:H2=3:1. The mixed gas enters the quartz tube filled with the magnetic catalyst to carry out a reverse water gas shift reaction to produce CO.
[0081] Example 6
[0082] Ferric nitrate, trimesic acid and deionized water were added to a beaker in a molar ratio of 1:1:80 and stirred until a uniform mixture was formed. Then, it was transferred to a hydrothermal autoclave and crystallized at 120°C for 20 hours. After cooling, the powder was obtained by high-speed centrifugation and washed several times with deionized water and C2H5OH respectively. Then, the obtained product was dried at 80°C for 12 hours to obtain the precursor Fe-MOF material.
[0083] The precursor Fe-MOF material was placed in a quartz tube, and the tube was purged with an inert atmosphere (Ar gas) for 2 hours, and then heat treated at 500° C. for 6 hours to obtain an immediate derivative magnetic catalytic material Fe / C.
[0084] The derived magnetic catalytic material and white carbon black (WCB) are pressed into tablets to obtain a magnetic catalyst with a diameter of 0.425 to 0.850 mm.
[0085] The magnetic catalyst is filled into a quartz tube, and the quartz tube is placed in the induction coil area of the induction heating equipment. The reaction pressure is normal pressure, the reaction temperature is the system temperature generated by the magnetic catalyst itself, the alternating frequency is 100KHz, and the raw material gas flow rate ratio is CO2:H2=3:1. The mixed gas enters the quartz tube containing the magnetic catalyst to perform a reverse water gas shift reaction to produce CO.
[0086] Example 7
[0087] Nickel nitrate, Fe powder, trimesic acid and DMF were added to a beaker in a molar ratio of 1:1:1:80 and stirred until a uniform viscous paste mixture was obtained. Then 1.44 ml of KOH solution (10 mol / L) was added to the resulting mixture, the pH value was adjusted to about 5, and stirred for 2 hours to partially remove the protonated tricarboxylic acid. It was then transferred to a hydrothermal autoclave and crystallized at 140 ° C for 30 hours. After cooling, the powder was obtained by high-speed centrifugation and washed several times with deionized water and C2H5OH respectively. Then, the obtained product was dried at 80 ° C for 12 hours to obtain the precursor FeNi-MOF material.
[0088] The precursor FeNi-MOF material was placed in a quartz tube, and the tube was purged with an inert atmosphere (Ar gas) for 2 hours. Then, it was heat treated at 550° C. for 3 hours to obtain the derived magnetic catalytic material FeNi / C.
[0089] The derived magnetic catalytic material and white carbon black (WCB) are pressed into tablets to obtain a magnetic catalyst with a diameter of 0.425 to 0.850 mm.
[0090] The magnetic catalyst is filled into a quartz tube, and the quartz tube is placed in the induction coil area of the induction heating equipment. The reaction pressure is normal pressure, the reaction temperature is the system temperature generated by the magnetic catalyst itself, the alternating frequency is 200KHz, and the raw material gas flow rate ratio is CO2:H2=3:1. The mixed gas enters the quartz tube containing the magnetic catalyst to perform a reverse water gas shift reaction to produce CO.
[0091] Example 8
[0092] 5g polyvinyl pyrrolidone (PVP, molecular weight 4000) was stirred evenly with 30mL H2O and 90mL ethanol, and then 10mmoL cobalt acetate was added thereto, and stirred for 5min to obtain a uniform mixed solution. Then, 5mmol potassium ferrocyanide was completely dissolved in 60mL H2O, and then added dropwise to the uniform mixed solution. After stirring for 1h, the mixed solution was allowed to stand at room temperature for 24h. Then, it was centrifuged, washed with deionized water and ethanol for 3-4 times respectively, and the washed catalyst was placed in an oven to dry. After drying, a metal precursor material was obtained, which was recorded as FeCo-MOF.
[0093] The obtained metal precursor material was placed in a quartz tube, and the tube was purged with an inert atmosphere (N2) for 2 hours, and then heat-treated at 300°C for 6 hours to obtain a magnetic catalyst, namely FeCo / CN.
[0094] The derived magnetic catalytic material and white carbon black (WCB) are pressed into tablets to obtain a magnetic catalyst with a diameter of 0.425 to 0.850 mm.
[0095] The magnetic catalyst is filled into a quartz tube, and the quartz tube is placed in the induction coil area of the induction heating equipment. The reaction pressure is normal pressure, the reaction temperature is the system temperature generated by the magnetic catalyst itself, the alternating frequency is 50KHz, and the raw material gas flow rate ratio is CO2:H2=3:1. The mixed gas enters the quartz tube containing the magnetic catalyst to carry out a reverse water gas shift reaction to produce CO.
[0096] Example 9
[0097] 5g polyvinyl pyrrolidone (PVP, molecular weight 4000) was stirred evenly with 30mL H2O and 90mL ethanol, and then 10mmoL nickel acetate was added thereto, and stirred for 5min to obtain a uniform mixed solution. Then 5mmol potassium ferrocyanide was completely dissolved in 60mL H2O, and then added dropwise to the uniform mixed solution. After stirring for 1h, the mixed solution was allowed to stand at room temperature for 24h. After centrifugation, the catalyst was washed with deionized water and ethanol for 3-4 times respectively, and the washed catalyst was placed in an oven to dry. After drying, the metal precursor material was obtained, which was recorded as FeNi-MOF.
[0098] The obtained metal precursor material was placed in a quartz tube, and the tube was purged with an inert atmosphere (N2) for 2 hours. Then, the material was heat treated at 700°C for 2 hours to obtain a magnetic catalyst, namely FeNi / CN.
[0099] The derived magnetic catalytic material and white carbon black (WCB) are pressed into tablets to obtain a magnetic catalyst with a diameter of 0.425 to 0.850 mm.
[0100] The magnetic catalyst is filled into a quartz tube, and the quartz tube is placed in the induction coil area of the induction heating equipment. The reaction pressure is normal pressure, the reaction temperature is the system temperature generated by the magnetic catalyst itself, the alternating frequency is 300KHz, and the raw material gas flow rate ratio is CO2:H2=3:1. The mixed gas enters the quartz tube filled with the magnetic catalyst to carry out a reverse water gas shift reaction to produce CO.
[0101] Example 10
[0102] 5g of polyvinyl pyrrolidone (PVP, molecular weight 4000) was stirred evenly with 30mL H2O and 90mL ethanol, and then 10mmoL of ferrous chloride was added thereto, and stirred for 5min to obtain a uniform mixed solution. Then, 5mmol of potassium ferrocyanide was completely dissolved in 60mL H2O, and then added dropwise to the uniform mixed solution. After stirring for 1h, the mixed solution was allowed to stand at room temperature for 24h. Then, it was centrifuged, washed with deionized water and ethanol for 3-4 times respectively, and the washed catalyst was placed in an oven to dry. After drying, a metal precursor material was obtained, which was recorded as FeFe-MOF.
[0103] The obtained metal precursor material was placed in a quartz tube, and the tube was purged with an inert atmosphere (N2) for 2 hours, and then heat-treated at 500°C for 3 hours to obtain a magnetic catalyst, namely FeFe / CN.
[0104] The derived magnetic catalytic material and white carbon black (WCB) are pressed into tablets to obtain a magnetic catalyst with a diameter of 0.425 to 0.850 mm.
[0105] The magnetic catalyst is filled into a quartz tube, and the quartz tube is placed in the induction coil area of the induction heating equipment. The reaction pressure is normal pressure, the reaction temperature is the system temperature generated by the magnetic catalyst itself, the alternating frequency is 200KHz, and the raw material gas flow rate ratio is CO2:H2=3:1. The mixed gas enters the quartz tube containing the magnetic catalyst to perform a reverse water gas shift reaction to produce CO.
[0106] The present invention is the first to use a magnetic induction catalytic reverse water-gas shift reaction (IC-RWGS) under an alternating magnetic field using a magnetic catalyst, and to prepare metal materials (Fe, Co, Ni and their composite materials) with magnetic properties. Under normal pressure and low ambient temperature conditions without external heating, the magnetic catalyst is acted on by a magnetic field to achieve the catalyst "charge-spin" synergistic catalytic reverse water-gas shift process. Since the reverse water-gas shift reaction is a strongly endothermic process, a higher reaction temperature is required. The reverse water-gas shift catalyst used in the magnetic induction system has both heating and catalytic effects, and can achieve excellent performance at lower temperatures. At the same time, it can avoid the problems of high energy consumption, low energy utilization, and uneven heating of traditional catalytic reactions.
[0107] The above description is only for the best embodiment of the present invention, but it should not be understood as limiting the claims. The present invention is not limited to the above embodiments, and its specific structure is allowed to be changed. However, all changes made within the protection scope of the independent claims of the present invention are within the protection scope of the present invention.
[0108] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.
Claims
1. A method for magnetic induction catalytic reverse water-gas shift, characterized in that: The following steps are involved: The magnetic catalyst and white carbon black are pressed into tablets to obtain a catalyst; The catalyst is placed in the induction coil area of the induction heating equipment, and a mixture of CO2 and H2 is introduced to perform a reverse water-gas shift reaction. The reaction pressure is normal pressure, and the alternating frequency is 50-300KHz to produce CO.
2. The method of magnetic induction catalytic reverse water-gas shift according to claim 1, characterized in that: Flow rate ratio CO2:H2=3:
1.
3. The method of magnetic induction catalytic reverse water-gas shift according to claim 1, characterized in that: The diameter of the catalyst is 0.425 to 0.850 mm.
4. The method of magnetic induction catalytic reverse water-gas shift according to claim 1, characterized in that: The magnetic catalyst is prepared by the following process: non-precious metal salt, metal element, organic ligand and solvent are mixed evenly, then the pH is adjusted to 5, standing for 20-30 hours or crystallizing at 120-180°C for 15-72 hours, centrifugal separation, washing, drying, and obtaining a metal precursor material; the metal precursor material is heat-treated and carbonized at 400-600°C for 2-10 hours under an inert atmosphere to obtain a magnetic catalyst.
5. The method of magnetic induction catalytic reverse water-gas shift according to claim 4, characterized in that: The non-noble metal salt is ferric chloride, ferrous chloride, ferric nitrate, cobalt chloride, cobalt nitrate or nickel nitrate.
6. The method of magnetic induction catalytic reverse water-gas shift according to claim 4, characterized in that: The metal element is Fe; the solvent is one of water, ethanol and N,N-dimethylformamide; and the organic ligand is terephthalic acid or trimesic acid.
7. The method of magnetic induction catalytic reverse water-gas shift according to claim 4, characterized in that: The molar ratio of the non-noble metal salt to the organic ligand is 1:1; the molar ratio of the metal element to the organic ligand is 1:1; and the inert atmosphere is argon.
8. The method of magnetic induction catalytic reverse water-gas shift according to claim 4, characterized in that: The magnetic catalyst is prepared by the following process: polyvinyl pyrrolidone, water and ethanol are stirred evenly, and then a metal salt is added to obtain a mixed solution, potassium ferrocyanide solution is added to the mixed solution, and after mixing evenly, the mixture is allowed to stand for 24 hours, centrifuged, and dried to obtain a metal precursor material, and the metal precursor material is heat-treated at 300-700°C for 2-6 hours under an inert atmosphere to obtain a magnetic catalyst.
9. The method of magnetic induction catalytic reverse water-gas shift according to claim 8, characterized in that: The dosage ratio of polyvinyl pyrrolidone, water, ethanol, metal salt and potassium ferrocyanide is 5g:30mL:90mL:10mmoL:5mmol.
10. The method of magnetic induction catalytic reverse water-gas shift according to claim 8, characterized in that: The metal salt is cobalt acetate, nickel acetate or ferrous chloride; the metal precursor material is heat treated at 300-700° C. for 2-6 hours under an inert atmosphere, and the inert atmosphere is nitrogen.
Citation Information
Cited By
Preparation method and application of metal-polymer hydrogen separation membrane with sandwich structure
CN120714459A